Spatial Pattern Separation Testing Differentiates Alzheimer’s Disease Biomarker-Positive and Biomarker-Negative Older Adults With Amnestic Mild Cognitive Impairment - Laczó, Martina; Lerch, Ondrej; Martinkovic, Lukas; Kalinova, Jana; Markova, Hana; Vyhnalek, Martin; Hort, Jakub; Laczó, Jan (Frontiers in Aging Neuroscience, 2021)
Background: The hippocampus, entorhinal cortex (EC) and basal forebrain (BF) are among the earliest regions affected by Alzheimer’s disease (AD) pathology. They play an essential role in spatial pattern separation, a process critical for accurate discrimination between similar locations. Objective: We examined differences in spatial pattern separation performance between older adults with amnestic mild cognitive impairment (aMCI) with AD versus those with non Alzheimer’s pathologic change (non-AD) and interrelations between volumes of the hippocampal, EC subregions and BF nuclei projecting to these subregions (medial septal nuclei and vertical limb of the diagonal band of Broca – Ch1-2 nuclei) with respect to performance. Methods: 118 older adults were recruited from the Czech Brain Aging Study. Participants with AD aMCI (n=37), non-AD aMCI (n=26), mild AD dementia (n=26) and cognitively normal older adults (CN; n = 29) underwent spatial pattern separation testing, cognitive assessment and brain MRI. Results: The AD aMCI group had less accurate spatial pattern separation performance than the non-AD aMCI (p=.039) and CN (p<.001) groups. The AD aMCI and non-AD groups did not differ in other cognitive tests. Decreased BF Ch1-2 volume was indirectly associated with worse performance through reduced hippocampal tail volume and reduced posteromedial EC and hippocampal tail or body volumes operating in serial. Conclusion: The study demonstrates that spatial pattern separation testing differentiates AD biomarker positive and negative older adults with aMCI and provides evidence that BF Ch1-2 nuclei influence spatial pattern separation through the posteromedial EC and the posterior hippocampus.